Marriage, children, houseownership and CPF on risk aversion in Singapore. - Wong, Soon Leong. (2010)
This study investigates the impact of four life-defining events: marriage, presence of child, homeownership and usage of cash and Central Provident Fund (CPF) for investments on risk aversion of individuals. By adopting a scenario-based approach to study how these events change attitudes towards risk, we find that risk aversion significantly increases after marriage and the arrival of first child. We also find that risk aversion decreases after the housing loan is fully paid off.